Exodus of clergy: A practical theological grounded theory exploration of Hatfield Training Centre trained pastors - Joynt, Shaun (HTS teologiese studies, 2013)
There is a shortage of clergy, at least in the Roman Catholic Church. Protestant churches in general are experiencing more of a distribution or placement challenge than a shortage. The two greatest hindrances to addressing the Protestant clergy distribution challenge are a lack of adequate compensation for clergy and the undesirable geographical location of a number of churches, as perceived by clergy. Influences such as secularisation, duality of vocation, time management, change in type of ministry, family issues, congregational and denominational conflict, burnout, sexual misconduct, divorce or marital problems, and suicide, affect clergy. Studies on the shortage of clergy have been conducted mostly in the USA and Europe and not in South Africa. This article focuses on the research gap by means of a practical theological grounded theory exploration of the exodus of clergy. Grounded theory methodology is used to identify the reasons why clergy trained at a Bible college of a Protestant charismatic mega church leave full-time pastoral ministry. Findings correspond to previous studies with two reasons appearing more frequently than others: responding to a call and leadership related issues. Firstly, respondents differed in their replies with respect to reconciling their exit from full-time pastoral ministry with their call. The replies included not being called, a dual call, or called but left anyway. Secondly, respondents indicated that leadership influence was mostly negative with regard to affirming their call.